The booster immunization using commercial vaccines effectively protect chickens against novel variants of infectious bursal disease virus (genotype A2dB1) - Chenyan Wang; Bo Hou (Poultry Science, 2024)
ABSTRACT: The novel variant IBDV (nVarIBDV, genotype A2dB1), characterized by bursal atrophy of fabricius and decreased lymphocytes, has been emerging on a large scale in Asia (including China) since late 2018. nVarIBDV is a new threat to the poultry industry, yet the currently licensed commercial vaccines, including the live viral vector vaccine, IBDV immune complex vaccine or VP2 subunit vaccine, are ineffective against nVarIBDV infection. In this study, specific-pathogen-free (SPF) chickens and broilers divided into 3 groups were vaccinated with the live viral vector vaccine, the VP2 subunit vaccine or the IBDV immune complex vaccine at 1 day-old, respectively. The SPF chickens received a secondary vaccination with the live B87 strain vaccine at 11-day-old. The bursa/body weight ratio, histopathology lesion of the bursa, and the differentiation between infected and vaccinated animals (DIVA) by qRT-PCR confirmed that the live viral vector vaccine or immune complex vaccine plus live B87 strain booster could provide at least 80% protection against the FJ2019-01 strain of nVarIBDV in SPF chickens. The broilers also received a secondary vaccination using a live W2512 G-61 strain vaccine at 14-day-old, and analyses showed that the VP2 subunit vaccine or immune complex vaccine plus the live W2512 G-61 strain booster also provided more than 80% protection against the FJ2019-01 strain of nVarIBDV. Unfortunately, the live viral vector vaccine plus live W2512 G-61 strain booster provided poor to moderate protection against FJ2019-01 in broilers. These findings suggest that combining commercial vaccines with rational booster immunization can effectively protect chickens against an nVarIBDV challenge.